Aktivitas Antioksidan Ekstrak Etanol Batang, Daun Dan Akar Kopasanda (Chromolaena odorata L) dengan Metode ABTS (2,2’- azino - bis (3-etilbenzotiazolin -6- asam sulfonat) - Astuti Amin; Soenandar Milian Tompunu Tengker; Wahyu Hendrarti (Jurnal Kimia Fullerene, 2022)
Kopasanda (Chromolaena odorata L.) is a plant that contains flavonoid compounds that can act as antioxidants. This study aims to determine the antioxidant potential of the ethanol extract of the stems, leaves and roots of kopasanda by looking at the IC50 value. The stems, leaves and roots of Kopasanda were extracted by maceration using 70% ethanol as solvent. The results of the antioxidant activity test using the ABTS method (2.2'- azino - bis (3 - ethylbenzothiazoline - 6- sulfonic acid) showed a very strong antioxidant activity with an IC50 value of 11.5380 g/ml leaves, 31.161 g/ml stems and 36,860 roots. g/ml with positive control of quarcetin obtained IC50 value of 1.698 g/ml. Based on these results, it can be concluded that the stems, leaves and roots of the encounter have very strong antioxidant activity against ABTS free radicals (2,2'- azino - bis (3 - ethylbenzothiazoline). - 6- sulfonic acid).